Mathematical modeling of aerodynamic behavior of antenna-mast structures when designing communication on railway transport - A. A. Loktev; V. V. Korolev; O. I. Poddaeva; K. D. Stepanov; I. Yu. Chernikov (Вестник Научно-исследовательского института железнодорожного транспорта, 2018)
Due to the development of high-speed operation, the problem of providing high-quality communication channels for train passengers, control and security systems, caused by the difﬁculty of fast positioning of the carriage, the large Doppler extension of the transmitted signal and the increasing amount of data transferred, is becoming especially topical at present. Two solutions can be conceptually possible in order to increase the coverage area near the railroad right-of-way: installation of a set of relatively small antennas of transmitting stations along the track or installation of powerful transmitters on high antenna-mast structures. Communication facilities exceeding 75 m are classiﬁed as particularly dangerous, technically complex communication facilities, and communication facilities exceeding 100 m, - as unique facilities. According to normative legal documents for structures classiﬁed as particularly dangerous, technically complex or as unique objects, it is necessary to additionally determine the aerodynamic coefﬁcients by blowing structures in wind tunnels or by recommendations developed by specialized organizations. In view of the above, it is relevant to solve the problem of developing recommendations for the determination of aerodynamic coefﬁcients and its approval as a guiding regulatory and technical document. This study is devoted to the development of a mathematical model for the behavior of an antenna-mast structure under wind inﬂuence, which would allow determining the aerodynamic coefﬁcients when collecting loads on newly designed or currently ope rated structures, and also adequately predict the behavior and condition of the object at various stages of the life cycle.